2017
DOI: 10.1016/j.envpol.2017.08.086
|View full text |Cite
|
Sign up to set email alerts
|

In situ benthic flow-through chambers to determine sediment-to-water fluxes of legacy hydrophobic organic contaminants

Abstract: Contaminated sediment can release hydrophobic organic contaminants (HOCs) and thereby act as a secondary source of primarily legacy hazardous substances to the water column. There is therefore a need for assessments of the release of HOCs from contaminated sediment for prioritization of management actions. In situ assessment of HOC sediment-to-water flux is currently done with (closed) benthic flux chambers, which have a sampling time exceeding one month. During this time, the water inside the chamber is deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…This may be because the effective diffusion coefficient of sand cap is 28 times lower than D bio . The result from the model was in accordance with the experimental studies . Granberg et al also showed that bioturbation can stimulate an augmented release flux of PCBs.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This may be because the effective diffusion coefficient of sand cap is 28 times lower than D bio . The result from the model was in accordance with the experimental studies . Granberg et al also showed that bioturbation can stimulate an augmented release flux of PCBs.…”
Section: Resultssupporting
confidence: 82%
“…The result from the model was in accordance with the experimental studies. 77 Granberg et al 78 also showed that bioturbation can stimulate an augmented release flux of PCBs. Figure 8 shows the flux at the surface of system under different combinations of properties of sorbent layer and bioturbation layer.…”
Section: Dimensionless Analysis Of Contaminant Diffusion In Capped mentioning
confidence: 99%
“…Dimethyl formamide (DMF) was used for sample cleanup, followed by 1 cm ø silica columns (10% deactivated). The cleanup method is described in detail by Mustajärvi et al (2017a). Following clean-up, the samples were reduced in volume (200 µL), and internal recovery standards (PCB53 and aldrin) were added prior to GCMS analysis.…”
Section: Sediment Spiking and Chemical Analysismentioning
confidence: 99%
“…Labeled internal surrogate standards (15 PAHs and 7 PCBs, see the Chemicals and materials section, Text ESI S1 †) were added to the combined extract (containing the rst and second extracts) and separately to the third extract. Clean up was done with dimethylformamide and a SiO 2 /H 2 O (10% Milli-Q water w/ w) column as described by Mandalakis et al 40 following the modications described by Mustajärvi et al 41 to include both PAHs and PCBs in the analysis. The extracts were reduced in volume prior to instrumental analysis and the recovery standards (PCB 53 and acenaphthylene) were added.…”
Section: Chemical Analysismentioning
confidence: 99%